Perancangan Perpustakaan Umum dan Galeri Seni dengan Gaya Arsitektur Regionalisme di Palembang - Suzzana Winda Artha Mustika; Reijavira Lamdha Fandji (Universitas Muhammadiyah Palembang, 2025)
The transformation of local culture in urban environments has become a challenge that continues to grow along with modernization. Cultural preservation is not only limited to maintaining the existence of existing urban heritage, but can also be realized through the design of new facilities as cultural development centers. One aspect of culture that has decreased is the habit of reading and appreciation of fine arts. Palembang City, as the capital city of South Sumatra Province, faces the challenge of increasing the level of literacy and art awareness which is still relatively low. Therefore, a literacy and art development center is needed, in the form of a public library and art gallery, which can be a means to increase public appreciation of local artworks and revive interest in reading culture as part of the city's cultural identity. The method used in this writing is a descriptive method by describing the existing conditions of the study object with contextual analys and identifying the concept and application of regionalism related to design needs. With an effort to create an expression of local culture packaged in modern technology and in harmony with the regionalism architecture approach. The output is expected to increase people's knowledge, provide easy access for people to enjoy library collections and works of art, and preserve the culture of Palembang city with an architectural approach.